Exploring Pediatric Nurses’ Perspectives on Their Work Environment, Work Attitudes, and Experience of Burnout: What Really Matters? - Buckley, Laura; Berta, Whitney; Cleverley, Kristin; Widger, Kimberley (Frontiers in Pediatrics, 2022)
Burnout is a psychological syndrome emerging as a prolonged response to chronic interpersonal stressors on the job. Paediatric nurses care for some of the most vulnerable patients in our healthcare system, and are themselves vulnerable to the impact of the stress of their work on their well-being. A thorough understanding of the underpinnings of the experience of workplace burnout for organizations is important, in the interests of mitigating or preventing this workplace outcome. Therefore, we sought to engage paediatric/neonatal critical care nurses to explore the thoughts and attitudes that elucidate their work experience through the following objectives: Objective 1: To explain and expand our understanding of paediatric critical care nurses experience of burnout in relation to their work environment and work engagement. Objective 2: To provide recommendations for nursing administrators to improve nurses’ work environment, work attitudes, and work outcomes. A convenience sample of paediatric critical care nurses from a large paediatric quaternary care hospital in Ontario, Canada were invited to participate in the study as part of the second phase of a sequential explanatory mixed-methods design. Semi-structured interviews were conducted and main themes and subthemes were distilled through the method of interpretive description. Results: A total of 18 PICU/CCCU/NICU nurses participated in the qualitative interviews. Derived themes included their experiences of burnout, including its prevalence and elusiveness. Their experiences of quality of work-life including themes such as compensation, emotional support at work, respect, their professional identity, and spill over into home life. They discussed components of work engagement, including the work itself, investment into their growth and development, and the meaning of their work. The self-care subthemes included the importance of preparation and recovery, and the use of physical and mental separation as a preservation strategy. Recommendations for strategies to mitigate burnout was summarized from the participants. Burnout is a complex and regularly occurring experience for paediatric critical care nurses. Although the experience may be difficult to identify, the impacts on the individuals are profound. Further research is needed to test practical interventions suggested by the participants themselves to pragmatically move forward with protecting the well-being of this population.